Smoking Cessation, Weight Gain, and Risk for Type 2 Diabetes: A Prospective Study - Lin Wu; Xiaowen Wang; Jia-Yi Dong; Yan-Ting Zhao; Hongqiang Lou (Frontiers Media S.A., 2022)
Objectives: To examine the association between smoking cessation and risk of type 2 diabetes with emphasis on post-cessation weight gain.Methods: In total, 8,951 participants from the China Health and Retirement Longitudinal Study at the baseline (2011) were included. Diabetes incidence was accessed at the third survey (2015). Current smokers were treated as the reference and odds ratios (OR) of type 2 diabetes for never smokers, recent, and long-term quitters were computed using multivariable logistic regression. Stratified analysis was further conducted by weight gain after smoking cessation.Results: There were 712 cases of type 2 diabetes identified. Compared with current smokers, the fully multivariable-adjusted ORs were 1.55 (1.02, 2.36) for recent quitters, 0.88 (0.61, 1.28) for long-term quitters, and 0.75 (0.59, 0.95) for never smokers. Stratified analysis showed recent quitters with weight gain of ≥2.0 kg had a significantly higher odds of type 2 diabetes [2.25 (1.02, 4.95)].Conclusion: The present study of the Chinese population suggested recent quitters with weight gain of ≥2.0 kg, compared with current smokers, had a significantly increased odds of type 2 diabetes.